Kalimat Imperatif Bahasa Jerman - Siska Sefrianthy Biring; Burhanuddin Burhanuddin; Abdul Kasim Achmad (Universitas Negeri Makassar, 2021)
Abstract. This study aims to obtain data on the ability to use imperative sentences in German students of class XI SMA Negeri 1 Palopo and the factors that affect students' ability to use imperative sentences. This type of research is descriptive. The population of this study were students of class XI MIPA 6. The sample of this study was class XI MIPA 6 which amounted to 34 students. The sample of this study was selected using total sampling. The research data were obtained through tests using imperative sentences and questionnaires. The results showed that the students' ability level in the use of imperative sentences in German was in the sufficient category (66%). The results of the questionnaire stated that the external factor that most influenced students' ability to use imperative sentences was family support that could improve students' German language skills (67.6%) and the internal factor that most influenced students' ability to use imperative sentences was that students had high motivation in following lessons. German especially imperative sentences (50%).